Ligand-mediated electron transfer in pH-tolerant Mn(II)/Fe(VI) bimetallic system: High-valent iron-oxo generation for efficient antibiotic removal - Jia-Xuan Ou-Yang; Xin-Jia Chen; Yu-Kun Huang; Jia-He Guo; Pi-Jun Duan; Xin-Yi Zhang; Chang-Wei Bai; Zhi-Quan Zhang; Jing Wang; Ming-Jie Huang; Ying Shao; Xiao-Wei Xu; et al. (Water Research, 2027)

Making waves: Rethinking membrane technologies for water remediation from a full-chain application perspective - Jing Wang; Chang-Wei Bai; Xin-Jia Chen; Zhi-Quan Zhang; Yu-Kun Huang; Xiao-Wei Xu; Pi-Jun Duan; Jin-Song Guo; Fei Chen (Water Research, 2026)

Rapid and sensitive on-site detection of PBoV G3 using an EsCas13d-based platform - Peng-fei Fu; Zhuo-wei Zhang; Jun Hong; An-xin Hu; Yi-yang Shi; Jia-wen Lin; Si-yi Pi; Yu-yan Zhang; Yan-hong Wang; Min Lu; Guo-you Yin; Dong-mei Wang (Analytica Chimica Acta, 2026)

High-surface-area g-C3N4/ZIF-8 heterojunction for synergistic radical and non-radical photocatalytic peroxymonosulfate activation toward antibiotic degradation: Mechanistic insight and membrane application - Ying-Ying Zhang; Si-Han Guo; Wu-He Ji Pi; Qing-Tong Dong; Qi Huang; Jing Bu; Li-Xuan Kou; Chun Li; Quan-Liang Chen (Journal of Environmental Chemical Engineering, 2026)

Mechanistic insights into the adsorption and separation of nonpolar molecules on delocalization porous carbon: Dispersion interactions enhanced by multiple bonds - Peixin Wang; Jingxu Tian; Da Wei; Yue Sun; Bo Liu; Wenji Pi; Jun Ma; Yunfeng Zhang; Hongyu Chen; Rui Shi; Yang Guo; Xiang Xu; et al. (Chemical Engineering Journal, 2026)

Platinum accumulation in chemotherapy: toxicity mechanisms, challenges, and mitigation strategies - Yier Lai; Guodong Qiu; Zhiwei Zheng; Xiaoting Huang; Pi Guo; Yuling Zhang; Ling Fang (BioMetals, 2026)
Platinum-based chemotherapeutic agents constitute the cornerstone of treatment for a wide range of solid tumors. However, residual platinum can persist in the body long after treatment cessation, leading to progressive accumulation, chronic multi-system toxicity, and significant impairment of patients' quality of life. The insidious onset and lack of specific monitoring methods often lead to the oversight of this treatment-related metal accumulation toxicity. This article reviews the environmental and occupational exposure risks of platinum, its unique pharmacokinetic properties, and elucidates how its irreversible binding to proteins and accumulation within mitochondria form the chemical basis for its long-term toxicity. It further elaborates on the core mechanisms underlying platinum accumulation-mediated multi-organ toxicity, including nephrotoxicity, neurotoxicity, and ototoxicity. The aim is to provide insights and directions for improving the long-term prognosis of cancer survivors by clarifying the toxicological mechanisms, clinical impacts, and future strategies for mitigating platinum-induced metal accumulation.

In vitro regeneration via indirect organogenesis from aseptic seedling-derived explants of the rare Tibetan medicinal shrub Sibiraea angustata - Mengting Pi; Xue Yu; Hongchang Li; Yali Guo; Wuyang Lai; Leipeng Cao; Tao Jiang; Lingxia Xu; Fuhua Peng; Hongdong Liu; Fei Wang; Jianguo Hu; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Paleoproterozoic Dongyaozhuang orogenic gold deposit in the Trans-North China Orogen: Constraints from in-situ U-Th-Pb dating of hydrothermal monazite and trace elements and sulfur isotopes of sulfides - Ying Ma; Shao-Yong Jiang; Ning Jin; Dao-Hui Pi; Yu Jiang; Guo-Hai Guo (Precambrian Research, 2026)

A single-cell perspective on polyethylene microplastic toxicity: linking fibroblast reprogramming to immune microenvironment alterations in the lung - Xiaoxuan Fan; Jingtian Liu; Shumin Huang; Xu Wang; Tianming Liu; Xiaochen Ma; Jiayi Zhou; Pi Guo; Yinge Wu (Journal of Hazardous Materials, 2026)

Prior-guided multi-domain mixture-of-experts for multimodal Earth observation data gaps - Chuang Liu; Jianhua Guo; Yingdong Pi; Xiao Wu; Zhiqi Zhang; Ru Chen; Xinyi Wang; Mi Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Iridium nanoparticles supported on titanium nitride with strong metal-support interaction toward efficient oxygen evolution reaction - Bosheng Zhang; Na Zhou; Panchao Zhao; Junqiu Guo; Hemu Pi (Fuel, 2026)

Climatic drivers of vector-borne diseases: A nationwide causal inference study in China - Xu Wang; Jiayi Zhou; Jingtian Liu; Ying Liang; Fei Lu; Linjing Zhang; Yunchong Yao; Xinyue Fang; Yangchun Zheng; Xiaobo Liu; Zhong Hu; Qingying Zhang; et al. (Environmental Research, 2026)

A Novel Cancer Driver Genes Identification Method Based on Self-Supervised Dual Masked Graph Autoencoder - Pi-Jing Wei; Xinhao Guo; Wenjun Li; Yun Ding; Rui-Fen Cao; Zhenyu Yue; Kanglin Wang; Chun-Hou Zheng (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Mapping plant cell-type-specific responses to environmental stresses - Muhammad Ali; Zhengjia Wang; Qiuyue Guo; Yixiang Wang; Yi Cai; Juan Du; Erxu Pi; Pingtao Ding; Jinbo Shen (Trends in Plant Science, 2026)

Buffer-free BOZn coordination sites enable efficient Fe(VI) oxidation for organic pollutant removal - Xin-Jia Chen; Yu-Kun Huang; Ning Li; Pi-Jun Duan; Chang-Wei Bai; Zhi-Quan Zhang; Jing Wang; Ying Shao; Xiao-Wei Xu; Jin-Song Guo; Fei Chen (Chemical Engineering Journal, 2026)

Research progress on the characteristics of milk allergens and the effect of Maillard reaction and its assistance treatment on allergenicity - Xiaowen Pi; Tanying Zhang; Jia Cao; Zeyu Peng; Bowen Li; Haozhe Yi; Wanxiang Guo; Jing Che; Chen Wang; Jinshen Chu (Food Chemistry, 2026)

Computational method of pile-soil interaction for offshore pile foundations considering scour effects - Xiao-ling Zhang; Xiao-zheng Guo; Pi-guang Wang; Cheng-shun Xu (Ocean Engineering, 2026)

Linking joint exposures to indoor and outdoor air pollution and residential greenness with male sperm quality: Based on human sperm banks from two provinces in China - Tingting Dai; Yunchong Yao; Xiaorong Li; Ruinian Zheng; Jiayi Zhou; Xu Wang; Jingtian Liu; Roumei Cai; Deshun Huang; Chunying Song; Tianqing Meng; Pi Guo (Journal of Hazardous Materials, 2026)

Catalytic hairpin assembly-assisted dual-enhanced SERS satellite nanocomplex for ultrasensitive detection of lipopolysaccharides in injection samples - Chan Huang; Xiuying Li; Xuan Zeng; Lingzhi Chen; Huabin Zhang; Xinjie Guo; Yiqun Chang; Wenshi Huang; Yichu Nie; Tianen Zhou; Jiaqi Yu; Jun Xu; et al. (Chemical Engineering Journal, 2026)

Impacts of cold spells on mortality risk in low-latitude subtropical plateau regions: a multi-dimensional analysis of spatial heterogeneity and vulnerability in Yunnan Province, China - Le-Yun Tan; Xian Tang; Yu-Hui Chen; Yang Chen; Qiu-Li Yu; Yuan-Yi Zha; Pi Guo; Qing-Ying Zhang (International Journal of Biometeorology, 2026)

Maternal exposure to indoor and outdoor air pollution during pregnancy increases offspring risk of autism spectrum disorder - Lingxi Wang; Wei Li; Yunchong Yao; Xiufang Jiang; Dongmei Ma; Yinxia Liu; Yunhua Deng; Lijiao Sun; Hong Li; Yuping Zhao; Guangyang Peng; Guo Wei; et al. (Environmental Research, 2026)

Immunosuppressive role of benzo[a]pyrene exposure in prostate cancer progression - Zhijin Zhang; Wentao Zhang; Huan Wang; Haotian Chen; Hong Wang; Yang Yu; Danjing Shen; Man Pi; Yang Wu; Ming Luo; Yanyan He; Shiyu Mao; et al. (Journal of Environmental Sciences, 2025)

Multimetallic intra-nanogap nanozyme-mediated lateral flow immunoassay for ultrasensitive and multimode detection of K. pneumonia in clinical samples - Weixia Zhi; Xinjie Guo; Yichu Nie; Lu Nie; Tingting He; Li Dai; Jing Xu; Xiangxin Zong; Jun Xu; Huaihong Cai; Yong Tang; Yanguang Cong; et al. (Chemical Engineering Journal, 2025)

Leaching model of an expanding coastal dumpsite considering climate change - Yijie Wang; Xiaoqing Pi; Vinay Yadav; Abid Hussain; Qian Liu; Yao Wang; Yuliang Guo; Yan Zhang; Xunchang Fei (Waste Management, 2025)

Association of coexposure to per- and polyfluoroalkyl substances and heavy metals with thyroid function across varied age pregnant women and the potential role of hemoglobin - Fang Wang; Xinyu Zhang; Yuxin Hu; Gang Wang; Jingbo Pi; Tingyu Wang; Haina Guo; Mingqi Zhang; Lijuan Zhang; Yuanyuan Xu (International Journal of Hygiene and Environmental Health, 2025)

3D self-supportive structures of micro/nanofiber assemblies constructed in situ in air turbulent flow fields for thermal protection at extreme conditions - Pi-Hang Yu; Yuan Gao; Guo-Dong Zhang; Chao Zhang; Chuan-Hui Guo; Seeram Ramakrishna; Yun-Ze Long; Jun Zhang (Chemical Engineering Journal, 2025)

La-doped bimetallic PCN-777 (La-Zr) catalyst synthesized by oil-bath heating for efficient oxidative desulfurization of dibenzothiophene - Mingyu Liao; Miaomiao Zheng; Gexian Li; Xiaolin Pi; Yuanjie Xiao; Linfeng Zhang; Huadong Wu; Jia Guo (Fuel, 2025)

Understanding the application-related features of sweet potato starch varying in multi-scale supramolecular structure - Yabin Guo; Dongling Qiao; Siming Zhao; Xiaowen Pi; Bowen Li; Kai Zhang; Binjia Zhang (Carbohydrate Polymers, 2025)

Mechanistic effects of surface functional groups on porous carbons for hydrogen purification: Multi-scale simulation perspective of competitive adsorption behavior - Hongyu Chen; Wenji Pi; Kueasook Ratchadaporn; Yang Guo; Zijie Sun; Changqing Su; Ziyuan Jiang; Xiang Xu; Zheng Zeng; Liqing Li (Chemical Engineering Journal, 2025)

Critical windows for exposure to chemical composition of ambient particulate matter and human semen quality decline - Lingxi Wang; Qiling Wang; Yunchong Yao; Jiayi Zhou; Xiaoyan Cai; Tingting Dai; Chunying Song; Yushan Li; Fuping Li; Tianqing Meng; Huiqiang Sheng; Pi Guo; et al. (Science of The Total Environment, 2024)

Insufficient Muscle Development Level Associated with Serum Zinc, Manganese and Cobalt Levels in Children Aged 6 to 9 Years in Shenzhen, China - Rimei Liang; Haide Zhu; Xiongcheng Cao; Yuheng Zeng; Yingbin You; Pi Guo; Qingying Zhang (Biological Trace Element Research, 2024)

Beneficial effect of residential greenness on sperm quality and the role of air pollution: A multicenter population-based study - Tingting Dai; Wei Li; Lingxi Wang; Jiayi Zhou; Kaixin Zhong; Yunchong Yao; Xiaoyan Cai; Linwei Tian; Haisheng Wu; Ting Xu; Lina Xiao; Haobo Ni; et al. (Science of The Total Environment, 2024)

Effects of dietary supplementation with fermented flaxseed meal on the growth performance, immune function, and intestinal microbiota of growing pigs - Lei Xu; Zixi Wei; Yao Guo; Baozhu Guo; Long Cai; Jingjiao Yan; Lianghua Ma; Wenjuan Sun; Yanpin Li; Xianren Jiang; Xilong Li; Yu Pi (Animal Feed Science and Technology, 2024)

Nickel-cobalt alloy oxide nanoparticles wrapped by carbon black for efficient oxygen evolution electrocatalysis - Bosheng Zhang; Panchao Zhao; Junqiu Guo; Hemu Pi (Fuel, 2024)

Interfacial solar evaporation driven Cd removal from contaminated sediments - Keyi Liu; Pan Wu; Yang Ye; Jiashu Jiang; Yuhao Guo; Yuejianshu Li; Xiong Yang; Yafei Shi; Gary Owens; Kewu Pi (Journal of Environmental Chemical Engineering, 2024)

Carbon dioxide adsorption capacity of porous carbon after polyamine impregnation under different pore structures and temperatures - Wenji Pi; Hongyu Chen; Yang Guo; Jinxian Wang; Xiang Xu; Zheng Zeng; Liqing Li (Chemical Engineering Journal, 2024)

A New Plastic Design Approach for the Vertical-Side-Plating Thickness of Ice-Strengthened Ships Suffering from Ice Floe Impacts - Mengying Mu; Kailing Guo; Wei Cai; Ling Zhu; Zhenyu Pi; Shuo Zhou (Journal of Marine Science and Engineering, 2024)
Ice-strengthened ships inevitably suffer from ice floe impacts during navigation in icy regions. Under some extreme-ice-impact loadings, the ship structure will experience plastic deformations. The magnitude of plastic deformation is highly correlated with the ice floe-impact energy level. During most ice impacts, only the ship’s plate undergoes minor plastic deformation. Considering that the structure still has a high structural strength with a minor permanent deformation, developing a structural plastic design method for polar ships has become a hot research issue in current studies. Therefore, in this paper, based on the rigid-plastic theory and the ice-crushing-energy approach, an experimentally verified theoretical model for predicting plastic deformations of the vertical-side plate of polar ship subjected to ice floe impacts was established. According to the analytical solutions of the plastic deformation, the plastic design formula to determine the plating thickness of ice-strengthened ships subjected to ice floe impacts was further derived based on the plastic design criteria. In addition, the parameter analysis of ice strength described by the ice pressure–area relationship, allowable-permanent-set parameter, impact energy and ice shape were conducted, and plating-thickness design curves with different design parameters were given. The design of plating thickness is very sensitive to the determinations of the allowable-permanent set and ice pressure–area curves. The designed plating thickness decreased with the increase of the allowable-permanent set. Moreover, a comparative analysis of the designed plating thickness for ice floe impact and rigid-mass impact was also carried out. Under the same impact conditions, due to energy absorption caused by ice damage, the designed thickness of the plate for rigid-mass impact was much larger than that for the ice impact. It is necessary to consider the impact-induced ice damage and energy dissipation in a structural design, instead of using rigid impact loads for conservative design. The research in this paper can provide some useful references for the structural design of ice-strengthened ships subject to ice floe impacts.

Systematical Evaluation of the Structure-Cardiotoxicity Relationship of 7-Azaindazole-based PI3K Inhibitors Designed by Bioisosteric Approach - Tianze Wu; Yi Chen; Chengbin Yang; Mingzhu Lu; Fang Geng; Jianhua Guo; Yan Pi; Yun Ling; Jun Xu; Tong Cai; Lei Lu; Yaming Zhou (Cardiovascular Toxicology, 2023)

A review on polyphenols and their potential application to reduce food allergenicity - Xiaowen Pi; Yuxue Sun; Jianjun Cheng; Guiming Fu; Mingruo Guo (Critical Reviews in Food Science and Nutrition, 2023)

An inulin-type fructan isolated from Serratula chinensis alleviated the dextran sulfate sodium-induced colitis in mice through regulation of intestinal barrier and gut microbiota - Zhenwei Li; Qiuyi Wen; Jiaju Pi; Daidi Zhang; Jinchun Nie; Wenlong Wei; Wei Li; De-an Guo (Carbohydrate Polymers, 2023)

Gain-of-function allele of HPY1 coordinates source and sink to increase grain yield in rice - Fengfeng Fan; Manman Liu; Nannan Li; Yu Guo; Huanran Yuan; Fengfeng Si; Mingxing Cheng; Gaili Chen; Meng Cai; Nengwu Li; Yixin Zhang; Yi Yu; et al. (Science Bulletin, 2023)

Sperm quality decline associated with gaseous pollutant exposure: Evidence from a large cohort multicenter study - Xiaoyan Cai; Haobo Ni; Qiling Wang; Tingting Dai; Lingxi Wang; Chunying Song; Yushan Li; Fuping Li; Tianqing Meng; Huiqiang Sheng; Lina Xiao; Ting Xu; et al. (Journal of Hazardous Materials, 2023)

Cotton-based bionic tree-shaped photothermal evaporator for extraction of heavy metals from river sediment - Keyi Liu; Yuejianshu Li; Pan Wu; Yuhao Guo; Yang Ye; Jiashu Jiang; Jiankai Hu; Xiong Yang; Yafei Shi; Gary Owens; Kewu Pi (Journal of Environmental Chemical Engineering, 2023)

Identification of RPD3/HDA1 Family Genes in Sugar Beet and Response to Abiotic Stresses - Qingyang Yu; Qianting Guo; Baizheng Li; Xiangxiao Tan; Liumin Wang; Shengnan Li; Zhi Pi (Sugar Tech, 2023)

Elevated serum lead and cadmium levels associated with increased risk of dyslipidemia in children aged 6 to 9 years in Shenzhen, China - Shufan Li; Ruiguo Liu; Yueyang Wu; Rimei Liang; Zhijiang Zhou; Jiaqi Chen; Yingbin You; Pi Guo; Qingying Zhang (Environmental Science and Pollution Research, 2023)

Elevated Interleukin-37 Associated with Dengue Viral Load in Patients with Dengue Fever - Jun-Ai Zhang; Jia-Jun Wang; Wen-Ting Zhang; Li Zhang; Bi-Ying Zheng; Gan-Bin Liu; Jing Liang; Yuan-Bin Lu; Xian-Jin Wu; Shu-Ying Yao; Guo-Ying Chen; Yun-Qi Xie; et al. (Current Microbiology, 2023)
Dengue remains a public health issue worldwide. Similar to chronic infectious diseases, stimulation of cytokine production is not enough to drive immune effector cells for effective virus clearance. One possible mechanism is the virus induces a large number of negative stimulatory cytokines inhibiting immune response. Interleukin 37 (IL-37) plays a crucial regulatory role in infection and immunity, inhibits innate and adaptive immunity as an anti-inflammatory cytokine by inhibiting proinflammatory mediators and pathways. To date, there are few studies reporting correlations between dengue fever (DF) and IL-37. In this study we found that the serum IL-37b and IL-37b-producing monocytes in patients were significantly increased in DF patients. A majority of the IL-37b produced by DF patients was produced by monocytes, not lymphocytes. Increased levels of IL-6, IL-10, and IFN-α were also found in DF patients. However, we failed to detect IL-1β, IL-17A and TNF-α in plasma, because of off-target. In our study, there was no relation between IL-6, IL-10, and IFN-α expressions and IL-37b in serum ( P > 0.05). The IL-37b-producing monocytes were negatively correlated with the level of IFN-α in serum and platelet count, and positively correlated with lymphocytes percentage ( P < 0.05, respectively). Additionally, serum DENV nonstructural protein 1 levels were positively correlated with monocytes percentages ( P < 0.05). Our data represents findings for IL-37b expression and its potential mechanisms in DF patients’ immune response.

Response of Vicia faba to short-term uranium exposure: chelating and antioxidant system changes in roots - Pi-xian Xiao; Xi Chen; Ning-ying Zhong; Ting Zheng; Ying-mei Wang; Guo Wu; Hong Zhang; Bing He (Journal of Plant Research, 2023)

Improving agricultural robot patch-spraying accuracy and precision through combined error adjustment - Hailong Li; Longzhe Quan; Yinghao Guo; Pengfei Pi; Yihui Shi; Zhaoxia Lou; Wei Jiang; Fulin Xia; Deng Sun; Yunhuan Yang; Wenchao Xu; Qian Chen (Computers and Electronics in Agriculture, 2023)

Global void ratio of municipal solid waste for compression indices estimation - Xiaoqing Pi; Xunchang Fei; Yao Wang; Xinlei Sun; Yuliang Guo (Waste Management, 2023)

Heat-induced changes in epitopes and IgE binding capacity of soybean protein isolate - Xiaowen Pi; Jiafei Liu; Yuxue Sun; Qingfeng Ban; Jianjun Cheng; Mingruo Guo (Food Chemistry, 2023)

Protein modification, IgE binding capacity, and functional properties of soybean protein upon conjugation with polyphenols - Xiaowen Pi; Jiafei Liu; Yuxue Sun; Qingfeng Ban; Jianjun Cheng; Mingruo Guo (Food Chemistry, 2023)

The size of the susceptible pool differentiates climate effects on seasonal epidemics of bacillary dysentery - Haobo Ni; Qinghui Zeng; Ting Xu; Lina Xiao; Xiaolin Yu; Jinrui Hu; Yang Li; Hualiang Lin; Pi Guo; Haijian Zhou (Science of The Total Environment, 2023)

The role of PIWI-interacting RNA in naringin pro-angiogenesis by targeting HUVECs - Yixing Pi; Zitian Liang; Qianzhou Jiang; Ding Chen; Zhikang Su; Yuanting Ouyang; Zhiyi Zhang; Jiaohong Liu; Siyi Wen; Li Yang; Tao Luo; Lvhua Guo (Chemico-Biological Interactions, 2023)

Characterization of the improved functionality in soybean protein-proanthocyanidins conjugates prepared by the alkali treatment - Xiaowen Pi; Yuxue Sun; Jiafei Liu; Xu Wang; Weichen Hong; Jianjun Cheng; Mingruo Guo (Food Hydrocolloids, 2023)

LncRNA-UC.25 + shRNA Alleviates P2Y14 Receptor–Mediated Diabetic Neuropathic Pain via STAT1 - Baoguo Wu; Congfa Zhou; Zehao Xiao; Gan Tang; Hongmin Guo; Zihui Hu; Qixing Hu; Hao Peng; Lingzhi Pi; Zhihua Zhang; Miaomiao Wang; Taotao Peng; et al. (Molecular Neurobiology, 2022)

The role of Th17 cells: explanation of relationship between periodontitis and COPD? - Jiaohong Liu; Yuanting Ouyang; Zhiyi Zhang; Siyi Wen; Yixing Pi; Ding Chen; Zhikang Su; Zitian Liang; Lvhua Guo; Yan Wang (Inflammation Research, 2022)

Effects of U on the growth, reactive oxygen metabolism and osmotic regulation in radish (Raphanus sativus L.) - Guo Wu; Xi Chen; Ting Zheng; Pi-xian Xiao; Ning-ying Zhong; Xiu-lin Yang; Yi Li; Wei Li (Environmental Science and Pollution Research, 2022)

Natural medicine combined with nanobased topical delivery systems: a new strategy to treat psoriasis - Zhiyue Zhao; Tao Liu; Shan Zhu; Jiaxin Pi; Pan Guo; Dongli Qi; Zhidong Liu; Nan Li (Drug Delivery and Translational Research, 2022)

Research for type 2 diabetes mellitus in endemic arsenism areas in central China: role of low level of arsenic exposure and KEAP1 rs11545829 polymorphism - Chenlu Fan; Zaihong Zhan; Xin Zhang; Qun Lou; Ning Guo; Mengyao Su; Yue Gao; Ming Qin; Liaowei Wu; Wei Huang; Meichen Zhang; Fanshuo Yin; et al. (Archives of Toxicology, 2022)

Associations between ambient heat exposure early in pregnancy and risk of congenital heart defects: a large population-based study - Xiaolin Yu; Huazhang Miao; Qinghui Zeng; Haisheng Wu; Yuliang Chen; Pi Guo; Yingxian Zhu (Environmental Science and Pollution Research, 2022)

Mortality risk attributable to diurnal temperature range: a multicity study in Yunnan of southwest China - Yujin Wang; Yang Chen; Jiaqi Chen; Rong Wu; Pi Guo; Shun Zha; Qingying Zhang (Environmental Science and Pollution Research, 2021)

Years of life lost with premature death due to ambient temperatures in a southwest plateau region of China: a cause-specific and individual characteristics stratified mortality study - Yujin Wang; Zan Ding; Changyu Deng; Pi Guo; Yingbin You; Liujiu Li; Yanfang Wang; Qingying Zhang (International Journal of Biometeorology, 2020)

Silver–bearing minerals in the Xinhua hydrothermal vein-type Pb-Zn deposit, South China - Minfang Wang; Xubo Zhang; Xiaonan Guo; Daohui Pi; Meijun Yang (Mineralogy and Petrology, 2018)

Mass spectrometry-guided isolation of two new dihydrobenzophenanthridine alkaloids from Macleaya cordata - Zhi-Xing Qing; Peng Yang; Kun Yu; Xue-Yi Yang; Jing-Hong Liu; Feng Xiang; Hua-Liang Cao; Pi Cheng; Jian-Guo Zeng (Natural Product Research, 2017)

Spatiotemporal evolution and driving forces of changes in rural settlements in the poverty belt around Beijing and Tianjin: a case study of Zhangjiakou city, Hebei Province - Pi-ling Sun; Yue-qing Xu; Qing-guo Liu; Chao Liu; Hong-liang Wang (Journal of Mountain Science, 2017)

TRPV1 attenuates intracranial arteriole remodeling through inhibiting VSMC phenotypic modulation in hypertension - Ming-Jie Zhang; Yun Liu; Zi-Cheng Hu; Yi Zhou; Yan Pi; Lu Guo; Xu Wang; Xue Chen; Jing-Cheng Li; Li-Li Zhang (Histochemistry and Cell Biology, 2017)

The critical role of ABCG1 and PPARγ/LXRα signaling in TLR4 mediates inflammatory responses and lipid accumulation in vascular smooth muscle cells - Xiaojie Cao; Lili Zhang; Chunhai Chen; Qingsong Wang; Lu Guo; Qinlong Ma; Ping Deng; Gang Zhu; Binghu Li; Yan Pi; Chunyan Long; Lei Zhang; et al. (Cell and Tissue Research, 2017)

Zircon U–Pb dating of Pubei granite and strontium isotope from sphalerite of the Xinhua Pb–Zn–(Ag) deposit, Yunkai Area of Guangxi Province, South China - Minfang Wang; Xubo Zhang; Daohui Pi; Xiaonan Guo (Acta Geochimica, 2016)

Mass spectrometry-guided isolation of two new benzoquinoline alkaloids from Macleaya cordata - Zhi-Xing Qing; Yu-Qin Xu; Peng Yang; Kun Yu; Pi Cheng; Jian-Guo Zeng (Natural Product Research, 2016)

Effectiveness of soil conservation methods in preventing red soil erosion in Southern China - Guo-Hua Zhang; Chong-Bao Xie; Xiao-Yu Pi; Chang-Qing Zuo (Journal of Mountain Science, 2015)

23,24-Dihydrocucurbitacin C: a new compound regarded as the next metabolite of cucurbitacin C - Zhi-Xing Qing; Yuan Zhou; Xiu-Bin Liu; Pi Cheng; Jian-Guo Zeng (Natural Product Research, 2014)

Amino Acid, Fatty Acid, and Metal Compositions in Edible Parts of Three Cultured Economic Crabs: Scylla paramamosain, Portunus trituberculatus , and Eriocheir sinensis - Ke-Ji Jiang; Feng-Ying Zhang; Yan Pi; Li-Li Jiang; Zhong-Li Yu; Dan Zhang; Man-Man Sun; Lu-Jiao Gao; Zhen-Guo Qiao; Ling-Bo Ma (Journal of Aquatic Food Product Technology, 2014)

Association between estrogen receptor alpha c.454-397T>C and c.454-351A>G and ischemic stroke risk: a systematic review and meta-analysis - Bing-Hu Li; Li-Li Zhang; Yan-Wei Yin; Yan Pi; Lu Guo; Qing-Wu Yang; Chang-Yue Gao; Chuan-Qin Fang; Jing-Zhou Wang; Jing Xiang; Jing-Cheng Li (Molecular Biology Reports, 2012)